The Role of Neuronal Factors in the Epigenetic Reprogramming of Microglia in the Normal and Diseased Central Nervous System - Veremeyko, Tatyana; Yung, Amanda W. Y.; Dukhinova, Marina; Strekalova, Tatyana; Ponomarev, Eugene D. (Frontiers in Cellular Neuroscience, 2019)
Twenty years ago, the scientific community exhibited relatively little interest in the study of microglial cells. However, recent technical and conceptual advances in this field have greatly increased interest in the basic biology of these cells within various neurodegenerative diseases, including multiple sclerosis, Alzheimer’s disease, and traumatic brain/spinal cord injuries. The main functions of these cells in the normal central nervous system (CNS) remain poorly understood, despite considerable elucidation of their roles in pathological conditions. Microglia populate the brain before birth and remain in close lifelong contact with CNS-resident cells under the influence of the local microenvironment. Within the CNS parenchyma, microglia actively interact with two main cell types, astrocytes and neurons, which produce many factors that affect microglia phenotypes in the normal CNS and during neuroinflammation. These factors include interleukin (IL)-34, macrophage colony-stimulating factor, transforming growth factor-β, and IL-4, which promote microglial expansion, survival, and differentiation to an anti-inflammatory phenotype in the normal CNS. Under inflammatory conditions, however, astrocytes produce several pro-inflammatory factors that contribute to microglial activation. The interactions of microglia with neurons in the normal and diseased CNS are especially intriguing. Microglia are known to interact actively with neurons by facilitating axonal pruning during development, while neurons provide specific factors that alter microglial phenotypes and functions. This review focuses mainly on the roles of soluble neuronal factors that affect microglial phenotypes and functions and the possible involvement of these factors in the pathology of neurodegenerative diseases.